Surgery for false aneurysm developing after type A acute aortic dissection. (November 2015) - Ergüneş, Kazım; Yilik, Levent; Yurekli, Ismail; Celik, Ersin; Gurbuz, Ali
Aortic false aneurysm is life-threatening with high morbidity and mortality rates. Surgical treatment varies according to the pathologic process, infection status, and site of origin of the aneurysm. We presented a case of false aneurysm of the ascending aorta, developing after type A acute aortic dissection repair. The operation was performed with the use of deep hypothermia and circulatory arrest to avoid massive uncontrollable hemorrhage.